Marketization in Long-Term Care: A Cross-Country Comparison of Large For-Profit Nursing Home Chains. (8th June 2017) - Harrington, Charlene; Jacobsen, Frode F; Panos, Justin; Pollock, Allyson; Sutaria, Shailen; Szebehely, Marta
This article presents cross-country comparisons of trends in for-profit nursing home chains in Canada, Norway, Sweden, United Kingdom, and the United States. Using public and private industry reports, the study describes ownership, corporate strategies, costs, and quality of the 5 largest for-profit chains in each country. The findings show that large for-profit nursing home chains are increasingly owned by private equity investors, have had many ownership changes over time, and have complex organizational structures. Large for-profit nursing home chains increasingly dominate the market and their strategies include the separation of property from operations, diversification, the expansion to many locations, and the use of tax havens. Generally, the chains have large revenues with high profit margins with some documented quality problems. The lack of adequate public information about the ownership, costs, and quality of services provided by nursing home chains is problematic in all the countries. The marketization of nursing home care poses new challenges to governments in collecting and reporting information to control costs as well as to ensure quality and public accountability.